Implementasi User Management Pada Laboratorium Dengan Primary Domain Controller Linux - Dhiemas Aditya Oktara; Rahmat Suhatman; Ibnu Surya (Journal of Applied Informatics and Computing, 2019)
The development of network technology now allows many applications that can be done with computer networks. This can be seen from the needs of educational institutions for computer networks. One of them is the Polytechnic Caltex Riau (PCR). The use of computers in the laboratory has not yet applied the concept of user management, so that the data stored on the computer can be accessed by more than one user which causes data to be reduced further. One way to overcome this problem is to implement a Primary Domain Controller (PDC), a server that can store and manage computer activities. Requires the client to have an account to log in to the computer and have their own storage media. From the test results obtained by the average received users log in, directory access and application by 96% and from the results of tests that have been done on average to CPU usage of 4% and memory usage by 37%. Can reduce from testing carried out to 30 users, using CPU and memory increases along with the number of clients who carry out activities and it takes a pause when logging in so that all users can access the server.